Dielectric properties of Pb[(1-x)(Zr1/2Ti1/2)- x(Zn1/3Ta2/3)]O3 ceramics prepared by columbite and wolframite methods - Banlue, Wanwimon; Vittayakorn, Naratip; Huang, Chien Chih; Cann, David P. (My University, 2008)
Polycrystalline samples of Pb[(1 - x)(Zr1/2Ti1/2) - x(Zn1/3Ta2/3)]O 3 , where x = 0.1-0.5 were prepared by the columbite and wolframite methods. The crystal structure, microstructure, and dielectric properties of the sintered ceramics were investigated as a function of composition via X-ray diffraction (XRD), scanning electron microscopy (SEM), and dielectric spectroscopy. The results indicated that the presence of Pb(Zn1/3Ta2/3)O3 (PZnTa) in the solid solution decreased the structural stability of overall perovskite phase. A transition from tetragonal to pseudo-cubic symmetry was observed as the PZnTa content increased and a co-existence of tetragonal and pseudo-cubic phases was observed at a composition close to x = 0.1. Examination of the dielectric spectra indicated that PZT-PZnTa exhibited an extremely high relative permittivity at the MPB composition. The permittivity showed a ferroelectric to paraelectric phase transition at 330 °C with a maximum value of 19,600 at 100 Hz at the MPB composition. © 2008 Springer Science+Business Media, LLC.